ELLIPSIS TYPES IN STEPHENIE MEYER’S “THE SHORT SECOND LIFE OF BREE TANNER” USING A SYNTACTIC ANALYSIS - Masniati, Andi - (ETERNAL (English, Teaching, Learning, and Research Journal), 2019)
Ellipsis is an omitting part of the sentence that may occur in the English novel. Some authors write a novel tend to use ellipsis in their work. Learners who read English novel are likely to find the author’s writing style which study is aimed to explain the types of the elliptical sentence used by the author in the novel The Short Second Life of Bree Tanner. This research applied a qualitative method and employed a source of data from Stephenie Meyer’s Novel and some references to support this study. A further technique of analyzing data in this research is always linked to the theory and methods based on Syntactic Analysis. Subsequently, this research uses the syntactic analysis form, Noam Chomsky. As a result, the researcher found that there are three types of elliptical sentence occurred in the novel. The types of elliptical sentence are a nominal ellipsis, verbal ellipsis, and clausal ellipsis. Therefore, based on the research findings, the researcher concludes that the types of ellipsis the author used in her novel based on the evidence are verbal ellipsis, nominal ellipsis, and clausal ellipsis. As a suggestion, it is essential to learn light on the readers or writers’ ability to employ ellipsis types in their work as it is necessary in more economizing and conceiving sentence.